Protective Action of Indapamide, a Thiazide-Like Diuretic, on Ischemia-Induced Injury and Barrier Dysfunction in Mouse Brain Microvascular Endothelial Cells - Tsuyoshi Nishioku; Fuyuko Takata; Atsushi Yamauchi; Noriko Sumi; Ikumi Yamamoto; Akiko Fujino; Mikihiko Naito; Takashi Tsuruo; Hideki Shuto; Yasufumi Kataoka (Elsevier, 2007)
The aim of the present study was to elucidate the effects of indapamide on ischemic damage to the blood-brain barrier (BBB) in vitro. The ischemia /reperfusion conditions employed here significantly decreased the viability of mouse brain capillary endothelial (MBEC4) cells, an effect ameliorated by indapamide. Ischemia increased the permeability of MBEC4 cells to two cellular transport markers, sodium fluorescein and Evan's blue-albumin. Indapamide reduced the ischemia-induced hyperpermeability of cells. These results suggest that indapamide may have a protective role against ischemia-induced injury and dysfunction of the BBB. Keywords:: indapamide, ischemia, blood-brain barrier